OPTIMALIZING STUDENTS’ SPEAKING SKILLS THROUGH THE MUHADATSAH PROGRAM: A CASE STUDY AT MTS KOTO TANGAH - Oktari, Sri Jomila; Zuyyina Ilmy Azizah; Hilmi, Danial (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2026)
This study aims to describe the implementation of the muhadatsah program in improving students’ Arabic speaking skills at MTs Koto Tangah, focusing on activity forms, instructional methods, managerial aspects, and supporting and inhibiting factors. The research employed a qualitative approach with a case study design. Data were collected through non-participant observation, semi-structured interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldana. The findings reveal that the muhadatsah program is regularly conducted outside formal Arabic lesson hours through various communicative activities such as paired dialogues, group discussions, role play, and short presentations. The program positively influences students’ speaking fluency, self-confidence, and frequency of Arabic use in daily interactions. However, several challenges remain, including weak language discipline, limited vocabulary, an underdeveloped Arabic language environment, and managerial constraints. Overall, the implementation of muhadatsah at MTs Koto Tangah aligns with the principles of Contextual Teaching and Learning and Communicative Language Teaching in developing students’ speaking skills.